Tactical Action Profile Of Indonesian Futsal Goalkeepers - Desrio Windoro; Rekha Ratri Julianti; Intan Primayanti (Kinestetik : Jurnal Ilmiah Pendidikan Jasmani, 2021)
This research aims to describe the overall tactical action profile of the national goalkeeper during the match. This research used observational research methods. The population of this study were 12 futsal teams which entered the national round, consisting of 8 male futsal teams and 4 female futsal teams with a total sample of 16 male goalkeepers and 8 female goalkeepers, total of 24 goalkeepers as samples. The results of this study show that the tactical action profile of the national goalkeepers futsal in the Nusantara Futsal League  as a whole. The goalkeeper s gave a hand gesture by pointing the opponent to guard the designated opponent as much as 60.35%. 5%, the goalkeeper s thrown a short ball to the defender by 37.28% goalkeeper, the goalkeeper s stopped the ball with his hands, when the ball came in the area behind his defense by 31.68%, the goalkeeper s stopped the ball with his feet, when the ball came in the back area defense 306 times (31.29%), when the corner kicked on the left or right side, the goalkeeper s instructed the player to cover as many goals as possible on his left or right side 237 times (24.3%), the goalkeeper away from the goal line to catch or ward off the ball carried out by the goalkeeper 81 times (8.28%), the goalkeepers caught the ball then kicks it directly towards the opposing team's goal 56 times ( 5.73%), the goalkeeper catches the ball and kicks it directly towards the opposing team's goal 27 times (4.77%), and the goalkeeper defends the defender 271 times (27.6%).  It be concluded that national goalkeepers tactical action profile in Indonesian Nusantara Futsal League  dominantly that the goalkeepers used sign by her / his hand to show theirs affairs nearby to the goal.